2019
DOI: 10.1111/clr.13516
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich osteotomy in atrophic mandibles: A retrospective study with a 2‐ to 144‐month follow‐up

Abstract: Objectives:The aim of the present retrospective study was to assess the long-term clinical outcome of sandwich osteotomy in pre-implant augmentation of atrophic mandible. Materials and methods:Sandwich osteotomies were performed in partially and fully edentulous mandibles of 63 consecutive patients in the present study. The vertical bone gain, graft stability, and marginal bone loss were measured radiographically.Implant survival and success rates were estimated in the follow-up ranged from 2 to 144 months (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Further, a safety margin of 4-5 mm above the nerve is required and keratinized tissue deficiency which limits the bone gain to a range of 4-8 mm in posterior mandible compared to 6-10 mm in the anterior mandible. [ 18 26 ] In our review the included studies showed comparable results with autologous and bone substitutes considering implant survival. Grafts placed in between the two osteotomized fragments are better able to integrate owing to the vascularization of native bone and as such no significant difference in implant survival could be observed.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Further, a safety margin of 4-5 mm above the nerve is required and keratinized tissue deficiency which limits the bone gain to a range of 4-8 mm in posterior mandible compared to 6-10 mm in the anterior mandible. [ 18 26 ] In our review the included studies showed comparable results with autologous and bone substitutes considering implant survival. Grafts placed in between the two osteotomized fragments are better able to integrate owing to the vascularization of native bone and as such no significant difference in implant survival could be observed.…”
Section: Discussionmentioning
confidence: 75%
“…[ 28 ] The basis being the intact vascularization provided by intact lingual mucoperisoteum and two osteotomized segments above the mandibular nerve. [ 26 ] The drawbacks of other augmentation procedures led Yeung in 2005 to use this technique for vertical augmentation of posterior mandible. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the data collection, only some authors replied to the e-mails sent to collect missing data. 37,50,58,62,64,73 A total of 1268 patients, receiving 4004 implants were included.…”
Section: Study Characteristicsmentioning
confidence: 99%